Spin dynamics : basics of nuclear magnetic resonance - Levitt, Malcolm H (John Wiley & Sons, 2001)
NMR spectroscopy is one of the most important and widely used techniques for the identification of compounds. Based on an established course this core text offers a truly modern and updated approach. Provides a comprehensive introduction to the subject Includes a multi-disciplinary approach, concentrating on basic principles and concepts Contains chapters of worked examples and problems to encourage a fuller understanding of topics Offers a pedagogical approach, starting with quarks and nucleons, and moving on to cover NMR imaging, COSY (Correlated Spectroscopy) and NOESY (Nuclear Overhauser Effect Spectroscopy). As a core subject in many science disciplines, this text will appeal to a wide range of students, as well as practising scientists and technicians. Assuming only a basic knowledge of complex numbers and matrices, it carefully and lucidly aids readers to fully understand this challenging subject.
Keywords: radiologie, nukleární medicína a zobrazovací metody; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární